Research on Network Security Attack Defense Mechanism and Its Development Trend - Yang, Xiulin (Transactions on Computer Science and Intelligent Systems Research, 2025)
In the digital era, network security has become a core issue concerning the global informatization process. This article first explores the current research progress in the field of network security from two dimensions: network attack and network defense. It systematically analyzes the classic methods of each. Then, this article delves into the application prospects of blockchain technology and reinforcement learning methods in network security. Blockchain technology, with its decentralized and immutable characteristics, provides a new solution path for enhancing network security. Reinforcement learning, through its adaptive mechanism and intelligent decision-making ability, demonstrates great potential in dynamic attack defense and intrusion detection. Finally, based on the aforementioned content, this article looks forward to the future development direction of this field. This article aims to provide systematic theoretical analysis and discussion for academic research and practical application in the field of network security, reveal the limitations of existing technologies and the application potential of frontier technologies, and provide new theoretical bases and technical directions for the construction of future network security defense systems.